"The interviews were transcribed", but how? Reflections on management research. Issue 4 (30th September 2019) - Nascimento, Leandro da Silva; Steinbruch, Fernanda Kalil
Abstract : Purpose: In qualitative research, it is recurrent to conduct data collection through interviews, which must be first transcribed for the data to be analyzed. Although there is a relationship between the stages of the interview and the data analysis, the link between them (i.e. the transcription) seems to be a neglected methodological procedure. This occurs because, in papers, it is generally reported that "the interviews were transcribed", without any details about the transcriptions conduction. From this methodological gap, this paper aims to discuss the relevance of detailing the methodological procedures adopted in the transcription in research reports in the management field. Design/methodology/approach: This paper takes the form of a methodological essay. Findings: The discussion focuses on the concepts of naturalized and denaturalized transcription, the relevance of adopting transcription norms and the need for reflexivity in conducting transcriptions – elements that must be explained in research reports to improve the methodological quality. Practical implications: This paper explores methodological details that management students and researchers can adopt when performing transcriptions. Consequently, journal editors and reviewers will have more subsidies on the methodological quality employed in researches, which contributes to a better evaluation process. Originality/value: This study demonstrates the relevance of a neglected methodological technique – transcription, which needs to be detailed in research reports, to contribute to the increase of methodological accuracy and to provide essential information to readers, allowing them to evaluate the rigor of the research. Thus, it is proposed that transcription should be considered a quality criterion in qualitative research.